Vertically Architectured Stack of Multiple Graphene Field‐Effect Transistors for Flexible Electronics. Issue 14 (14th November 2014) - Meng, Jie; Chen, Jing‐Jing; Zhang, Liang; Bie, Ya‐Qing; Liao, Zhi‐Min; Yu, Da‐Peng
<x xml:space="preserve">Abstract</x> Vertically architectured stack of multiple graphene field‐effect transistors (GFETs) on a flexible substrate show great mechanical flexibility and robustness. The four GFETs are integrated in the vertical direction, and dually gated GFETs with graphene channel, PMMA dielectrics, and graphene gate electrodes are realized. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>